Polymers as Hi-Tech Materials - Adhikari, Basudam (Indian Science Cruiser, 2009)
Polymers have captured the top position in today's Hi-Tech devices by virtue of their hght weight, low cost and superior performances. Invention of efficient catalysts and modern technological revolution has expanded the horizon of growth of polymer products from a limited area of petrochemical-based synthetic classical polymers. Although sustained efforts could successfully develop thermally and environmentally stable as well as strong polymers until early eighties but people started realizing the global problem of disposal of such non-biodegradable polymeric solid wastes. However, matured and intensive research has gifted today very high performance as well as biodegradable polymers, ranging from products for general purpose applications such as polymers in agriculture to highly specialized and sophisticated polymer products for biomedical engineering. Today electrically conducting polymers, viz., polyaniline, polacetylene etc., are considered as synthetic metals and have made outstanding contribution in various semiconductor devices and sensors. Photoconductive behaviour of poly (vinyl carbazole) has been exploited in today's photo-copying equipment vis-a-vis piezo-electric and pyro-electric properties of poly (vinylidene fluoride) are utilized in transistors, loudspeakers, and detectors. Separation andpurification technology of water and organic solvents has been enriched with the use of ionomers in one side to the use of segmented polyurethanes on the other. Intelligent polymers has made it possible to develop thermoresponsive ON-OFF switch controlled drug delivery device in biomedical field such as artificial pancreas and in cell sheet engineering for myocardial tissue reconstruction. Classical poljrmers today have appeared in different form and nature as modern poljrmers. Revolutionary developments and tailoring have provided polymers for light weight, strong and attractive packaging applications. Modern polyolefins, viz., LLDPE with high elongation in machine direction, good tear strength at cross direction and excellent puncture resistance; less crystalline VI^DPE grades (with 0.880- 0.912 g/cm^) are ideal polymers for a variety of low-temperature film applications such as ice and frozen-food packaging. PVDC and ethylene vinyl alcohol polymer-based oxygen barrier films are being used to package red meat and baked goods.